The role of the Indonesian child protection commission in the Papua province conflict - Asemki, Yuspani; Purwaningsih, Titin (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Amid mounting concerns surrounding child welfare, particularly in Papua Province, this study urgently investigates the efficacy of the Indonesian Child Protection Commission (KPAI) in safeguarding this vulnerable demographic. With a primary objective to assess the protection measures for Papuan children aged 6-18, the research aims to elucidate their developmental trajectories and highlight the imperative for heightened protective interventions. Employing qualitative methods, data sourced from prominent media outlets including Kompas, Suara Papua, Jubi, Detik, and CNN are meticulously analyzed using the Nvivo 12 Plus Application. The findings starkly expose a pervasive lack of attention and security afforded to Papuan children by pertinent institutions, consequently exposing them to elevated social risks, such as alcoholism, promiscuity, and substance abuse. Notably, despite its designated mandate, the current role of KPAI appears inadequate, particularly in times of conflict, exacerbating the vulnerability of Papuan children and magnifying their potential as social liabilities. These findings underscore the exigent need for immediate and concerted efforts to rectify these systemic deficiencies and fortify the protective infrastructure for Papuan children, thereby ensuring their holistic well-being and thwarting potential social threats.